2001
DOI: 10.1136/adc.85.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and developmental effects of otitis media with effusion into the teens

Abstract: No previous study considering behaviour problems as an outcome has followed children long enough to determine whether some of the early sequelae of OME are still present in the early to late teens. Some developmental sequelae of OME, particularly deficits in reading ability, can persist into late childhood and the early teens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(155 citation statements)
references
References 15 publications
5
147
0
3
Order By: Relevance
“…We observed a slight decrease in effect size when we controlled for the extent of childhood otitis media (Tables 4 and 5), but a significant proportion of variance was still explained by PTA. The remaining effects were independent of, and additional to, the well-established effects of otitis media (18).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We observed a slight decrease in effect size when we controlled for the extent of childhood otitis media (Tables 4 and 5), but a significant proportion of variance was still explained by PTA. The remaining effects were independent of, and additional to, the well-established effects of otitis media (18).…”
Section: Discussionmentioning
confidence: 86%
“…Hearing threshold appears to depend partly upon history of otitis media in childhood (15). Furthermore, history of otitis media is associated with poor performance in language and academic areas during childhood (16,17), behavioral problems during childhood (17), and behavior and language during adolescence (18). As such, we were careful to consider the degree of otitis media in our study of the effects of hearing level on the four areas described.…”
Section: Identification Of Signals In Noisementioning
confidence: 99%
“…10 Very long-term effects of the condition remain unknown. The Paradise trial follow-up on 9-to 11-year-olds concluded that there were no demonstrable longterm disabilities in their selected sample, 25 whereas an earlier paper by Bennett et al 15 reported that some developmental effects persist into teenage years, particularly on reading ability. In the main, however, these study data support the importance of potential child benefit for interventions aimed principally at short-to medium-term outcomes for evaluation in clinical trials.…”
Section: Impact Of Otitis Media With Effusion On Children Over Timementioning
confidence: 99%
“…OME leads to variable and intermittent hearing loss and delays in language and behaviour development, and remains the most common reason for surgery in children. [13][14][15] While the trial of alternative regimens in glue ear treatment (TARGET) is currently clarifying the role for surgery in restricted and persistent cases, there is therefore (and likely to remain) a need for medical treatments for useful temporising management that either aid natural resolution or could be used prior to or as an alternative to surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most common bacterial infections in the field of otolaryngology having significant economic and individual repercussion [1].…”
Section: Introductionmentioning
confidence: 99%